Environmental & architectural phenomenology. Vol. 4, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 1993)
Vol. 4, No. 3, Fall 1993 (includes “items of interest,” "citations received,” poem by Richard Kahoe, and essays by Michael Brill, Fran Violich & Tom Jay).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals